Perang Sampit (Konflik Suku Dayak Dengan Suku Madura) Pada Tahun 2001 - Sifaun Nadzifah (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
The Sampit War was a war between the Dayak and Madurese tribes which culminated in February 2001. The factors that triggered the Sampit war were cultural differences or customs between the Dayak and Madura tribes which eventually became the cause of conflict between the two. The conflict between the Dayak and the Madurese had repeatedly occurred during the New Order era, but the peak of the conflict only exploded in the Reformation era. Many factors trigger conflict, which is mainly caused by socio-cultural causes. The clash between these two tribes has caused many casualties on the part of the Madurese and forced them to leave Central Kalimantan. This study aims to determine the causes and effects of the Sampit war in 2001. This study uses a qualitative method with a descriptive approach using data research results in the form of several books, archives, documents, journals and the internet with the hope that through this method can find data that accurate